Cryogenic neutron protein crystallography: routine methods and potential benefits. (1st August 2014) - Coates, Leighton; Tomanicek, Stephen; Schrader, Tobias E.; Weiss, Kevin L.; Ng, Joseph D.; Jüttner, Philipp; Ostermann, Andreas
Abstract : The use of cryocooling in neutron diffraction has been hampered by several technical challenges, such as the need for specialized equipment and techniques. This article reports the recent development and deployment of equipment and strategies that allow routine neutron data collection on cryocooled crystals using off‐the‐shelf components. This system has several advantages compared to a closed displex cooling system, such as fast cooling coupled with easier crystal mounting and centering. The ability to routinely collect cryogenic neutron data for analysis will significantly broaden the range of scientific questions that can be examined by neutron protein crystallography. Cryogenic neutron data collection for macromolecules has recently become available at the new Biological Diffractometer BIODIFF at the FRM II and the Macromolecular Diffractometer (MaNDi) at the Spallation Neutron Source, Oak Ridge National Laboratory. To evaluate the benefits of a cryocooled neutron structure, a full neutron data set was collected on the BIODIFF instrument on a Toho‐1 β‐lactamase structure at 100 K.